Multisection DFB Tunable Laser Based on REC Technique and Tuning by Injection Current - Renjia Guo; Jun Lu; Shengping Liu; Yuechun Shi; Yating Zhou; Yutao Chen; Jia Luan; Xiangfei Chen (IEEE Photonics Journal)
Based on the reconstruction-equivalent-chirp technique and tuning only by the injection current, a multisection DFB tunable laser is demonstrated experimentally. At the temperature of 20 °C, each laser can be tuned at about 3.4–3.6 nm with a side-mode suppressing ratio (SMSR) of over 35 dB from 30 to 170 mA, and the tuning speed is about 10–30 ms, which is much faster than that by the thermoelectric cooler. The results may help to realize very low cost tunable lasers in the future.